Metaphors and Monsters. A literary-critical study of Daniel 7 and 8 - Porter, Paul A. (1983)
Doctoral Dissertation for the Degree of Doctor of Theology, University of Uppsala; 16-29: š. izbu and historical omens; 69-120: Mesopotamian herd leaders.